Does drip irrigation contribute to the economic sustainability of soybean production? - Toffanin, Arianna; Maucieri, Carmelo; Rossi, Giampaolo; Paulon, Graziano; Trestini, Samuele; Borin, Maurizio (Italian Journal of Agrometeorology, 2024)
A two-year (2020, 2022) field experiment on soybean was conducted in northeaster Italy to evaluate the effect of irrigation (drip irrigation vs. rainfed), soil amendment (compost vs. digestate) and a cover crop (triticale vs. no cover crop) on grain yield and quality. Highly different rainfall amounts (627 mm and 258 mm in 2020 and 2022, respectively) and similar ET0 (578 mm and 581 mm in 2020 and 2022, respectively) were recorded during the growing seasons. Irrigation was managed using the web platform Irriframe suppling 51 mm in 2020 and 157 mm in 2022. Irrigation was the only experimental factor with significant effects on soybean grain yield and quality, except soil amendment on aboveground biomass production. In 2020, drip irrigation had no significant effect on grain yield (4.6 Mg ha-1 on average), while it increased it by 157% in 2022 compared to the rainfed control (1.0 Mg ha-1). The grain protein content was reduced by irrigation (43.2 ± 1.3% and 42.6 ± 0.9% under rainfed and irrigation managements, respectively). No treatment effect was observed on the grain oil content. A positive effect of irrigation was observed on water use efficiency, with values ranging from 0.40 ± 0.19 kg m-3 to 0.71 ± 0.12 kg m-3. The balance of the economic sustainability of drip irrigation was negative in both years: this irrigation method was not sustainable for soybean within the economic framework of the study area at the time. However, the results also confirmed that irrigation is a key agronomic technique to reduce production variability and dryland vulnerability of soybean.